RELATIONSHIP PARENTING AND MENTORING ONLINE LEARNING FOR SCHOOL AGE DURING THE COVID-19 PANDEMIC IN TANGERANG WEST JAVA - Safira, Nabila Aisyah; Jaeudin, Jaeudin (Universitas Airlangga, 2021)
ABSTRACT Backgrounds:Due to the increasing spread of the corona virus in Indonesia, the government immediately took action to stop the spread of the virus, one of which was by imposing online learning (on the network) so that students did learning at home accompanied by parents so that parenting patterns for children should be more effective. intense. At this time parental assistance is needed to help children in learning through online.Objective: The purpose of this study was to determine the relationship between parenting styles and children's learning assistance during the COVID-19 pandemic in Sepatan Village Rt 01/05 Sepatan District. Research Methods: The type of research used in this study is quantitative research using a descriptive correlation research design using a cross sectional approach. The sample is taken using the Solvin formula and using a random sampling technique. Research Results: From the results of the bivariate analysis using the chi square test, the results obtained a significance value (2-sided) or